Case Report: A Grievous Tale Of A Rare Primary Thyroid Leiomyosarcoma - Wan Nabila Wan Mansor; Norhaslinda Abdul Gani; Khairul Azlan Shahril Abu Dahari; Aliza Ahmad; Rohaizam Japar Jaafar (Springer open, 2024)
Indexed by Scopus